The epistemic judgement framework: a reflexive tool for physical education teachers’ professional development to support Quality Physical Education - Grecic, D.; Sprake, A.; Thomson, A.; Christodoulides, E.; Palmer, C. (Frontiers in Education, 2024)
The need for Quality Physical Education to provide the many benefits the subject offers is well established. Unfortunately, in too many areas ineffective teaching and learning practices are limiting the profession’s response to children’s developmental needs. Many teachers’ professional development interventions are criticised as not enabling the required philosophical, and pedagogical shifts that are needed to improve practice and student outcomes. The paper presents a new integrated model, the Epistemic Judgement Framework to enhance this process. Epistemology offers an important lens by which to explore teacher beliefs and behaviors, however, existing research in this field is very specific in scope, which makes learning transfer difficult. To better explore this area a fuller appreciation of the bioecological environment in which teaching takes place as well as the Critical Realist view of the teaching world is introduced. The purpose of this article therefore is to propose a framework to guide teacher professional development to support the achievement of Quality Physical Education that merges environmental considerations and exploration of hidden influencers with epistemological research on teacher decision making and behavior. Practical applications for teacher professional learning utilizing the model and future directions are suggested.